Avaliação das relações entre iluminação ambiente e a saúde e bem estar de usuários: proposta metodológica utilizando câmera climática - Tamura, Cintia Akemi (2017)
Recommendations related to indoor illumination generally adopt metrics focused on illuminance, even though more complex issues should be accounted for, such as visual perception, circadian rhythm and thermal sensation, among others. In this context, tests were performed in a rotating climate chamber during three seasons of the year (winter, spring and summer) with n = 16 (height 1.80m, SD = 0.06, body weight 80 kg, SD = 8.9, age 24.9 years, SD = 3.6). Three types of lighting were evaluated: two natural (equatorial and non-equatorial lighting) and artificial lighting. Each subject was exposed during three days of testing to each type of lighting, over the three seasons and from 8 a.m. to 1 p.m. During this time, the thermal comfort index PMV was monitored, and ranged between +0,5 e = 0,5 (comfort conditions). The following environmental variables were recorded: horizontal illuminance (lux), correlated color temperature (K), dominant wavelength (nm), and circadian action factor (acv), and the individual variables were: vertical illuminance (lux), electro dermal activity (EDA) and skin temperature (° C). Objective data were statistically correlated with subjective responses to questionnaires related to lighting and thermal perception as regards the indoor environment. Main findings suggest an inverse Spearman correlation (rs=-.544) between CCT and participants' expectations regarding the indoor thermal conditions, corroborating the heat-hue theory. Another correlation found, this time inversely proportional between DWI values and participants' expectations regarding indoor thermal conditions, showed a contradiction with respect to recommendations for maintenance of circadian regulation and individual preferences, since higher values of DW1 would be adequate for thermal comfort, but not to circadian functions. Finally, it was observed that Tsk increased during each session (8 a.m. to 1p.m.), when subjects were exposed to natural light, with statistically significant correlations Pearson r=.504 (equatorial façade exposure) and r=.502 (non-equatorial façade exposure), and virtually no correlation for artificial lighting (r=-.151). Such finding indicates that the characteristics of color temperature, dominant wavelength and circadian action factor of natural light may have been responsible for melatonin suppression during exposure.